Photoactive Molecular‐Based Devices, Machines and Materials: Recent Advances. Issue 42 (22nd October 2018) - Baroncini, Massimo; Canton, Martina; Casimiro, Lorenzo; Corra, Stefano; Groppi, Jessica; La Rosa, Marcello; Silvi, Serena; Credi, Alberto
Abstract : Molecular and supramolecular‐based systems and materials that can perform predetermined functions in response to light stimulation have been extensively studied in the past three decades. Their investigation continues to be a highly stimulating topic of chemical research, not only because of the inherent scientific value related to a bottom‐up approach to functional nanostructures, but also for the prospective applications in diverse fields of technology and medicine. Light is an important tool in this context, as it can be conveniently used both for supplying energy to the system and for probing its states and transformations. In this microreview we recall some basic aspects of light‐induced processes in (supra)molecular assemblies, and discuss their exploitation to implement novel functionalities with nanostructured devices, machines and materials. To this aim we illustrate a few examples from our own recent work, which are meant to illustrate the trends of current research in the field. Abstract : A bright future: the combination of the concepts and tools of photophysics and photochemistry with appropriately designed molecular and supramolecular systems can lead to the realization of nanoscale devices, machines and materials that can execute sophisticated functions in response to light stimulation.